A study of Radiographic Features and Patterns of Pulmonary Tuberculosis: HRCT - Khalid , Qurat ul ain; Hina, Gull e; Rana, Faiza; Noor, Izza; Javed, Nauman; Samreen, Kubra (Medical Science Journal for Advance Research, 2023)
Background: PTB is becoming more prevalent across the world. A significant research area would seem to be the evaluation of PTB findings on HRCT. Objective: Using the high-resolution computed tomography to investigate pulmonary tuberculosis in patients. Material and Methodology: A cross-sectional study was carried out at Al-Amin diagnostic center, Gondal Hospital, and Chattha Hospital. Each patient accomplished a written informed consent form preceding the HRCT examination. In this study, 103 patients had the procedure; all of them had PTB, and the results of their examinations were analyzed using HRCT. The mean age of the patients was 49.9. The eligibility of the patients was assessed using the inclusion criteria. Results: Consequences from 103 patients with PTB revealed that n=64 (62.1%) were men and n=39 (37.9%) were women, with the highest ratio being n=19 (18.4%) among patients in the 31–40 age range. The most frequent clinical symptom of PTB was Productive cough (22.5%). The respective HRCT findings were revealed in the cases under investigation nodules 17.4% and cavitation 15.4%. Conclusion: In the investigation, PTB impacted men and patients in the 31–40 age groups more frequently than women. The predominant HRCT findings of patients among PTB were nodules, cavitation, and lymphadenopathy. The HRCT outcomes were more closely related to the right lung and right superior lobe.